Using GRACE and hydrological data to estimate changes of evapotranspiration in the Three Gorges Reservoir. Issue 1 (February 2021) - Zheng, Yuhao; Wang, Linsong; Fu, Zhengyan; Peng, Zhenran; Chen, Chao
Abstract: The Three Gorges Project (TGP) has driven changes in water storage, which directly affected the migration and redistribution of land water in the Yangtze River Basin. As a result, a new water balance is established, regional or local evapotranspiration fluctuates, and it may change the climate and weaken geological stability. In this study, we use data from GRACE gravity satellites, hydrological models, remote sensing, and in-situ observations to monitor the spatiotemporal evolution of terrestrial water changes and in the Three Gorges Reservoir (TGR) area, and then to estimate the evapotranspiration induced by water storage fluctuations in the TGR. We calculated the downscaled GRACE results based on the Land Surface Models (LSMs) and scale factor method, which can improve the signal amplitude and spatial differences in the study area and its surrounding areas. Combining the scaled GRACE-derived total water storage changes, precipitation and surface runoff, our estimated evapotranspiration (ET) in the TGR area is highly consistent with the MOD16 global ET results from 2002 to 2016. Seasonal ET changes are mainly driven by climate and rainfall, but GRACE-derived ET shown that the fluctuations of evapotranspiration are also affected by artificial water storage directly, e.g., in the main three water impounding stages (2003, 2006, and 2008), the elevation of the water level caused an abnormal increase in regional ET, but during the water drainage period (spring and autumn), high precipitation did not have a great impact on ET. Our results show that the coverage area of the reservoir area and the short-term fluctuations of the reservoir capacity are the main factors determining the ET in the TGR area.